Assessing the electrochemical performance of a supercapacitor electrode made of copper oxide and activated carbon using liquid phase plasma. Issue 1 (2017) - Kim, Hangun; Kim, Byung-Joo; , Young-Kwon Park; Jung, Sang-Chul
No abstract available